Letter from Roger Casement to Richard Morten, discussing a Feis he attended, his health and his plan to attend an Orange gathering, - Casement, Roger, 1864-1916 (1905)
Casement described the Feis as "first rate" even if one of the speakers was absurd. Casement complains about the state of his health and jokes that he will be wearing a green tie at an Orange gathering on 12th July in Armagh and "probably be stoned to death" for it.